Microstructural Characterization of Dissimilar Titanium Alloys Joints Using Ni/Al Nanolayers - Sónia Simões (2018)
This study demonstrates the potential of the use of Ni/Al nanolayers for joining dissimilar titanium alloys. For this purpose, a detailed microstructural characterization of the diffusion bonding interfaces of TiAl to Ti6Al4V, TiAl to TiNi and TiNi to Ti6Al4V was carried out. The nanolayers (alternated aluminum and nickel (Ni-7V wt.%) layers) were deposited onto the base material surfaces. Diffusion bonding was performed at 700 and 800 degrees C under pressures ranging from 5 to 40 MPa and at dwell times between 60 and 180 min. Microstructural characterization was performed using high resolution transmission and scanning electron microscopies. The results revealed that dissimilar titanium joints (TiAl to Ti6Al4V, TiAl to TiNi and TiNi to Ti6Al4V) assisted by Ni/Al nanolayers can be obtained successfully at 800 degrees C for 60 min using a pressure of 20 MPa. The bond interfaces are thin (less than 10 mu m) and mainly composed of NiAl grains with a few nanometric grains of Al8V5. Thin layers of Al-Ni-Ti intermetallic compounds were formed adjacent to the base materials due to their reaction with the nanolayers.